1991
DOI: 10.1093/rheumatology/30.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Defects of the Retinal Pigment Epithelium in Scleroderma

Abstract: We completed ocular examination, including retinal fluoroangiography, in 19 unselected patients with diffuse systemic sclerosis (scleroderma) and compared the findings with those made in 50 consecutive patients with systemic lupus erythematosus, 18 with primary Sjögren's syndrome, 20 with mixed connective tissue disease, and 20 healthy women. Five of 19 scleroderma patients had atrophy of the retinal pigment epithelium (26.3%) while none of the controls and only four of the 88 (4.5%) patients with other connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…It was suggested that atrophy of RPE was likely to be because of an underlying abnormality and damage of the choroidal vasculature at the choriocapillary level. 25,26 In our study, there were no detectable retinal changes in our patients with scleroderma. It has been reported that retinal arterioles are relatively unaffected in patients with scleroderma.…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…It was suggested that atrophy of RPE was likely to be because of an underlying abnormality and damage of the choroidal vasculature at the choriocapillary level. 25,26 In our study, there were no detectable retinal changes in our patients with scleroderma. It has been reported that retinal arterioles are relatively unaffected in patients with scleroderma.…”
contrasting
confidence: 47%
“…It has been reported that retinal arterioles are relatively unaffected in patients with scleroderma. 20,25,26 Pericytes of nerves are important structures in pathophysiology of scleroderma and retinal arterioles are less sensitive to scleroderma due to the fact that retinal arterioles do not have nerve supply. 25 On the other hand, choroid vessels have nerve supply and pericytes.…”
mentioning
confidence: 99%
“…Opportunities for this level of exchange likely materialized as a result of the common niche that S. enterica subspecies I share. These salmonellae are usually isolated from warmblooded animals, whereas other non-group I strains are isolated generally from reptiles (8,31). Our further observation that the entire 1.1 kb of mutS and flanking sequences appear to have Compatibility matrix of the total mutS matrix showing pairwise comparisons of informative binary sites within (colored triangles) and between (white) the intragene segments indicated.…”
Section: Niche Overlap and R-m Compatibility As Potential Factors Delmentioning
confidence: 87%
“…In chicken, the pecteneal glia express glutamine synthetase (GS) and vimentin (Vim) but not glial fibrillary acidic protein (GFAP; Gerhardt et al 1999aGerhardt et al , 1999b. The transcription factor Pax2 is expressed by glial cells during the ontogeny of the vertebrate ON thereby inhibiting the neuronal fate and promoting astroglial differentiation (Krauss et al 1991;Püschel et al 1992;Soukkarieh et al 2007). It is maintained in differentiated astrocytes in fish, chick and mammals (Chan-Ling et al 2009;Parrilla et al 2009;Stanke et al 2010) but apparently is downregulated in adult (aged) mammals (Chu et al 2001;Mi and Barres 1999).…”
Section: Introductionmentioning
confidence: 99%